Current Trends in Cross-Border Funding for Microfinance - Lahaye, Estelle (CGAP, Washington, DC, 2014)
In 2011, cross-border funders committed at least US$25 billion to microfinance or financial services for the poor. CGAP research shows that levels of cross-border funding continued to increase despite the global financial crisis and strained national budgets, but at a much lower growth rate, indicating that cross-border funders were adjusting to the new environment. The analysis of the global trends in the microfinance funding landscape in this brief is based on data from CGAP's surveys of cross-border funders.